Tourism Accessibility And Inclusive Tourism Influences OnGovernment Policies In Karo Regencies, Sumatera Utara, Indonesia - Hamdani, Muhammad; Erlina, Erlina; Purwoko, Agus; Rujiman, Rujiman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to determine: 1) the influence of tourism accessibility on government policies in Karo Regency; 2) the influence of inclusive tourism on government policies in Karo Regency; and 3) the influence of tourism accessibility and inclusive tourism on government policies in Karo Regency. This was descriptive research using a quantitative approach. The total number of sample was 214, taken by using Slovin's method. The data was analyzed by using multiple regression analysis, using SPSS program. The results showed that there is an influence of tourism accessibility on government policies in Karo Regency, there is an influence of inclusive tourism on government policies in Karo Regency, and there is an influence of tourism accessibility and inclusive tourism on government policies in Karo Regency.